The salt- and drought-inducible poplar GRAS protein SCL7 confers salt and drought tolerance in Arabidopsis thaliana - Ma, Hong-Shuang (Oxford University Press, 2010)
The plant-specific GRAS/SCL transcription factors play diverse roles in plant development and stress responses. In this study, a poplar SCL gene, PeSCL7, was functionally characterized in Arabidopsis thaliana, especially with regard to its role in abiotic stress resistance. Expression analysis in poplar revealed that PeSCL7 was induced by drought and high salt stresses, but was repressed by gibberellic acid (GA) treatment in leaves. Transient expression of GFP-PeSCL7 in onion epidermal cells revealed that the PeSCL7 protein was localized in the nucleus. Transgenic Arabidopsis plants overexpressing PeSCL7 showed enhanced tolerance to drought and salt treatments. The activity of two stress-responsive enzymes was increased in transgenic seedlings. Taken together, these results suggest that PeSCL7 encodes a member of the stress-responsive GRAS/SCL transcription factors that is potentially useful for engineering drought- and salt-tolerant trees.